Antecedents and obstacles to e-banking adoption: a comparative study of India and Kenya. (8th March 2011) - Nyangosi, Richard; Arora, J.S.
The banking sector across the globe is embracing e-banking technologies and using as a part of business strategy for expansion, revenue increase, extension of customer network and creating perfect competition among financial service institutions. This paper is an effort to investigate bankers' perceived need, methods they use to motivate customers and perceived challenges of e-banking adoption. The data for this study were obtained from a survey which was conducted in India and Kenya in the fourth quarter of 2006 and in the first three quarters of 2007. When comparing the two countries, it was inferred that Indian and Kenyan bankers' considered e-banking adoption as a very important step to be taken currently. Further analysis indicated that the high adoption cost, lack of proper infrastructure in banks, privacy issues and fear of rapid rise in e-crimes were the most significant at 5% level indicating that this factors were mostly affecting the growth and adoption of e-banking.